Effect of heat treatment on the electrochemical behavior of AA2055 and AA2024 alloys for aeronautical applications - Rivera Cerezo, Heriberto; Gaona Tiburcio, Citlalli; Cabral Miramontes, José Ángel; Bautista Margulis, Raúl German; Nieves Mendoza, Demetrio; Maldonado Bandala, Erick; Estupiñan López, Francisco Humberto; Almeraya Calderón, Facundo (Molecular diversity preservation international, 2023)
Since their development, third-generation aluminum–lithium alloys have been used in aeronautical and other applications due to their good properties, replacing conventional Al-Cu and Al-Zn alloys and resulting in an increase in payload and fuel efficiency. The aim of this work was to investigate the influence of different heat treatments on the electrochemical corrosion behavior of the alloys AA2055 and AA2024 in the presence of three different electrolytes at room temperature, using an electrochemical noise (EN) technique in accordance with the ASTM-G199 standard. In the time domain, the polynomial method was employed to obtain the noise resistance (Rn), the localization index (IL), skewness, and kurtosis, and in the frequency domain, employing power spectral density analysis (PSD). The microstructure and mechanical properties of the alloys were characterized using scanning electron microscopy (SEM) and the Vickers microhardness test (HV). The results demonstrated better mechanical properties of the AA2055 alloy, which had a Vickers hardness of 77, 174, and 199 in the heat treatments T0, T6, and T8, respectively. An electrochemical noise resistance (Rn) of 2.72   105 W cm2 was obtained in the AA2055 T8 alloy evaluated in a NaCl solution, while the lowest Rn resistance of 2.87   101 W cm2 occurred in the AA2024 T8 alloy, which was evaluated in a HCl solution. The highest electrochemical noise resistance (Rn) was obtained in the AA2055 alloys, which had received the T6 and T8 heat treatments in the three solutions.